Characterization of collagen type I/tannic acid beads as a cell scaffold. (March 2021) - Baldwin, Andrew; Uy, Lisa; Booth, Brian W
Breast cancer is the most commonly diagnosed cancer among women worldwide. Surgical removal of tumors is often necessary and many patients suffer complications due to subsequent breast reconstruction. A safe and effective breast reconstructive material is needed for patients recovering from surgical removal of small breast cancer tumors. Our lab has developed injectable collagen/tannic acid beads seeded with patient-derived preadipocytes for regeneration of healthy breast tissue in patients post-lumpectomy. Previous research indicates that the inclusion of tannic acid in the matrix imparts an anticancer property. This research seeks to determine the variables needed to control collagen/tannic acid bead diameter and seeded cell attachment, which are essential to proper bead implantation and function. We found that as tannic acid concentration increases within the beads, cell attachment decreases. Bead diameter is controlled by bead generator voltage, solution osmolality, the degree of cell attachment, and tannic acid concentrations. Higher voltages resulted in significant decrease in bead diameter. Collagen/tannic acid beads decreased in diameter when placed in solutions of increasing osmolality. Higher degrees of cell attachment across the surface of the beads were associated with a significant decrease in diameter. In beads made with high concentrations of tannic acid, bead diameter was found to decrease. Collagen/TA beads are a promising subdermal tissue regenerative matrix with anticancer activity as an alternative to simple lipofilling in breast reconstructive procedures. This study was conducted to better understand the properties of collagen/TA beads in order to improve injection efficacy and tissue regenerative activity.